2008
DOI: 10.3201/eid1405.071675
|View full text |Cite
|
Sign up to set email alerts
|

New Saffold Cardioviruses in 3 Children, Canada

Abstract: In Canada, cardiovirus isolates related to Saffold virus were detected in nasopharyngeal aspirates from 3 children with respiratory symptoms. Polyprotein sequence of the Can112051-06 isolate had 91.2% aa identity with Saffold virus; however, EF and CD loops of the viral surface varied substantially.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
88
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(91 citation statements)
references
References 12 publications
2
88
0
Order By: Relevance
“…SAFV has been detected in stool and respiratory-secretion samples from children with gastroenteritis (Chiu et al, 2008; (Abed & Boivin, 2008;Chiu et al, 2008) and non-polio acute flaccid paralysis , as well as in asymptomatic individuals Chiu et al, 2008;Xu et al, 2009;Zoll et al, 2009). In several cases, SAFV has been detected in addition to other viruses known to cause gastroenteritis, thus hindering interpretation regarding SAFV infection and observed pathology (Chiu et al, 2008;Drexler et al, 2008;Ren et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…SAFV has been detected in stool and respiratory-secretion samples from children with gastroenteritis (Chiu et al, 2008; (Abed & Boivin, 2008;Chiu et al, 2008) and non-polio acute flaccid paralysis , as well as in asymptomatic individuals Chiu et al, 2008;Xu et al, 2009;Zoll et al, 2009). In several cases, SAFV has been detected in addition to other viruses known to cause gastroenteritis, thus hindering interpretation regarding SAFV infection and observed pathology (Chiu et al, 2008;Drexler et al, 2008;Ren et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Since its initial discovery in 2007 from a stool sample collected in 1981 in California, USA (Jones et al, 2007), SAFV has been detected in stool and respiratory samples from patients in Europe, North and South America and Asia (Abed & Boivin, 2008;Blinkova et al, 2009;Chiu et al, 2008;Drexler et al, 2008;Liang et al, 2008;Ren et al, 2009;Xu et al, 2009;Zoll et al, 2009). Currently, there are eight SAFV genotypes based on variants of the VP1 protein (SAFV-1-8), which is a determinant of viral tropism and antibody-neutralization sensitivity .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…reports of SAFV (TMEV species) in human faeces and respiratory specimens (Abed & Boivin, 2008;Drexler et al, 2008Drexler et al, , 2011Jones et al, 2007;Nielsen et al, 2012;Zoll et al, 2009), almost all cardiovirus testing is for animal specimens in the context of EMCV epizootics (Maurice et al, 2005). Recent studies have reported EMCV infection in two human cases from Peru (Oberste et al, 2009) and 21 % EMCV seroprevalence among persons sampled in the same area of Peru (Czechowicz et al, 2011).…”
Section: (A) the Radial Tree Shows The Distribution Of Ev Species (Evmentioning
confidence: 99%
“…2b), was the overall third most common virus found among study subjects. SAFV2, detected in North and South America, Europe and Asia, has been the most commonly identified genotype to date (Abed & Boivin, 2008;Blinkova et al, 2009;Chiu et al, 2008;Drexler et al, 2008;Itagaki et al, 2010;Zoll et al, 2009). SAFV2 has been associated with respiratory disease (Abed & Boivin, 2008;Chiu et al, 2008) and with invasive disease, including two fatalities (Drexler et al, 2011;Nielsen et al, 2012).…”
Section: (A) the Radial Tree Shows The Distribution Of Ev Species (Evmentioning
confidence: 99%